Transits maghrébins à Istanbul. Trajectoires, profils et stratégies - Jean-François Pérouse (Revue des Mondes Musulmans et de la Méditerranée)
Since the beginning of the 1990’s, Istanbul has become a focal point, both polarizing and re-dispatching the flows in the international transit migration system set up between Europe and poor countries. We have chosen to focus on the Maghrebis (from Libya to Morocco, including Mauritania), even though they represent a rather small “group”, compared to Iraqis or Iranians. By examining their survival strategies and their effort to build an ephemeral community in transit, we try to point out the diversity of transit experiences, the weight of national identities, the efficiency of familial ties, the problems of entering the metropolitan labor market and the reshaping of gender relations.